Function of Construction Waste as A Replacement Material for Stones in Stone Column - Vijayasimhan, Sivapriya; N, Sivakumar; J, Dhanushvarman; S, Gokul; M, Rakesh Raj (International Journal of Sustainable Construction Engineering and Technology, 2025)
Sustainability is an important aspect of the Civil engineering domain and mainly focuses on the reduction of carbon footprints. One of the major contributors to carbon footprint is construction and demolition (C&D) waste, which increases with urbanisation. With an increase in awareness of recycling, the usage of C&D waste is used as a replacement material for stones in a stone column. The stone column is a conventional ground improvement technique used to stabilise the soil by improving its strength and settlement behaviour. The C&D waste of M30-graded crushed concrete and the brick is considered and used as a replacement material to make columns of two consistencies (0.4 and 0.6). The other waste material of C&D waste is removed and crushed to a size of 5 mm and used as a column material. A load-penetration study is conducted in California Bearing ratio (CBR) mould by developing a column in the center of the mould with 100% of conventional aggregate, crushed concrete and bricks which is compared with the virgin clay. Due to the interlocking behaviour of the column materials, the initial behaviour of the load-penetration behaviour follows the same pattern. With an increase in load intensity, the load bearing of crushed concrete is similar under higher consistency. As the water retention of brick is more for lower consistency, the load bored by 100% crushed brick is the same as that of stone aggregate. There is almost 4 times increase in the strength of composite ground compared with virgin clay. Making the zero-value material more useful by creating a circular economy.